The Role of Entrepreneurship Education and the Profil Pelajar Pancasila Strengthening Project in Mediating Self-Efficacy on Entrepreneurial Spirit - Rima Tri Vijayanti; Anika, Asia (Universitas Negeri Semarang, 2025)
This research aims to determine the role of entrepreneurship education and the Projek Penguatan Profil Pelajar Pancasila in mediating self-efficacy toward the entrepreneurial spirit of 11th-grade students at SMA Negeri 15 Semarang. The theoretical foundation used in this research is social cognitive theory. This study employs a quantitative approach with a causal design. The population comprises 352 11th-grade students at SMA Negeri 15 Semarang for the 2023/2024 academic year. A sample of 188 students was taken using the Slovin formula with a 5% margin of error. Data was collected through questionnaires and analyzed using descriptive statistical methods and SEM with SmartPLS version 4.1.0.4. The results indicate that the research model meets the validity and reliability of SEM constructs. Entrepreneurship education, the Profil Pelajar Pancasila strengthening project, and self-efficacy positively and significantly influence the entrepreneurial spirit. Self-efficacy also has a positive indirect effect through entrepreneurship education and the Projek Penguatan Profil Pelajar Pancasila.